Pelatihan Pengembangan Bahan Ajar Berbasis Aplikasi Android pada SMP N 3 Kupang - Butar-Butar, Agustina; Manu, Rolens E H Riwu; Yewang, Markus U K; Br Simanungkalit, Erika F.; Mau Manek, Alfridus; Abineno, Mises B.C (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
The learning process at SMP Negeri 3 Kupang is still teacher-centered, making students less motivated to learn. Teachers also rarely use technology-based learning media. Learning media must be packaged as attractively as possible so that students can easily understand the material. Therefore, the right teaching material that can support student learning according to current developments is Android-based mobile learning. The lack of variety in the media shared is not solely the teacher's fault, but because teachers are not optimizing technological developments. Therefore, it is necessary to carry out training in developing teaching materials based on Android applications at SMP N 3 Kupang. . The method for implementing this service consists of an initial survey to measure teachers' initial understanding regarding the development of interactive teaching materials based on Android applications, then planning the development of interactive teaching materials based on Android applications. Implementation activities include: Explanation/Coaching clinic, Training and practice in developing interactive teaching materials based on applications Android, data analysis and finally evaluation or reflection. Based on the evaluation results of this activity, there were 80% of teachers who mastered this material.